Acute 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin exposure in adult mice does not alter the morphology or inflammatory response of cortical microglia. (18th January 2021) - Lowery, R.L.; Latchney, S.E.; Peer, R.P.; Lamantia, C.E.; Opanashuk, L.; McCall, M.; Majewska, A.K.
Highlights: Acute TCDD exposure does not affect microglial baseline characteristics in vivo . Acute TCDD exposure does not prime microglial immune response in vivo . Central and peripheral immune cells are differentially affected by TCDD. Abstract: Microglia, the immune cells of the brain, have a canonical role in regulating responses to neurological disease or injury, but have also recently been implicated as regulators of neurophysiological processes such as learning and memory. Given these dual immune and physiological roles, microglia are a likely mechanism by which external toxic stimuli are converted into deficits in neuronal circuitry and subsequently function. However, while it is well established that exposure to environmental toxicants negatively affects the peripheral immune system, it remains unknown whether and how such exposure causes neuroinflammation which, in turn, may negatively impact microglial functions in vivo . Here, we examined how acute 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) exposure in adulthood, which negatively impacts immune cells in the periphery, affects microglial characteristics in the cortex of the mouse. We found that microglia density, distribution, morphology, inflammatory signaling, and response to a secondary, pathological activation were unaffected by acute TCDD exposure. These results suggest that acute, peripheral TCDD exposure in adulthood is not sufficient to induce an overt inflammatory phenotype in cortical microglia.